[The failure of Western technology in Asia review] - Noor, Abdun (1984)
A review of Doh Joon-Chien, Eastern Intellectuals and Western Solutions: Follower Syndrome in Asia (New Delhi: Vikas Publishing House Pvt. Ltd., 1980).
Keywords: Book reviews